Neighborhood Latino ethnic density and mortality among HIV-positive Latinos by birth country/region, Florida, 2005–2008. Issue 3 (3rd May 2016) - Sheehan, Diana M.; Trepka, Mary Jo; Fennie, Kristopher P.; Dillon, Frank R.; Madhivanan, Purnima; Maddox, Lorene M.
ABSTRACT: Objective. Lower mortality for Latinos has been reported in high Latino density areas. The objective was to examine the contribution of neighborhood Latino density to mortality among HIV-positive Latinos. Methods. Florida HIV surveillance data for 2005–2008 were merged with the 2007–2011 American Community Survey data using zip code tabulation areas. Hazard ratios (HR) were calculated using multi-level weighted Cox regression and adjusted for individual-level factors and neighborhood poverty. Results. Of 4649 HIV-positive Latinos, 11.8% died. There was no difference in mortality risk across categories of Latino ethnic density for Latinos as a whole. There were subgroup effects wherein mortality risk differed by ethnic density category for Latinos born in some countries/regions. Residing in an area with ≥50% Latinos compared with <25% was associated with increased mortality risk for Latinos born in Puerto Rico (HR 1.67; 95% confidence interval [CI] [1.01–2.70]). Residing in an area where Mexicans were the majority Latino group was associated with increased mortality risk for Latinos born in Mexico (HR 3.57; 95% CI [1.43–10.00]). Conclusions. The survival advantage seen among the Latino population in high Latino density areas was not seen among HIV-positive Latinos. Research is needed to determine if this may be related to stigma or another mechanism.